2012
DOI: 10.1111/j.1447-0594.2011.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Both conventional indices of cognitive function and frailty predict levels of care required in a long‐term care insurance program for memory clinic patients in Japan

Abstract: In outpatients of a memory clinic, care ranks, which define the upper limit of monthly benefit in the Japanese LTCIP, were influenced by age, cognitive function, frailty and living arrangements. Understanding the relationship among these parameters would be useful in predicting the needs of cognitively impaired patients and important when comparing the possible services provided by long-term care systems for them worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Takechi et al . examined 201 cognitively impaired patients and found that their mean grip strength was 16.9 kg, much lower than the healthy older adults . We have also observed that cognitively impaired older adults had lower muscle mass, slower gait speed and weaker grip strength .…”
Section: Introductionmentioning
confidence: 68%
“…Takechi et al . examined 201 cognitively impaired patients and found that their mean grip strength was 16.9 kg, much lower than the healthy older adults . We have also observed that cognitively impaired older adults had lower muscle mass, slower gait speed and weaker grip strength .…”
Section: Introductionmentioning
confidence: 68%
“…Nursing care services are offered based on the support‐need or care‐need level. However, there are substantial numbers of people with dementia and family caregivers who do not wish to use social care services or apply for certification . These participants were classified in the “did not apply” group, and they were assumed to have met the lowest level of care required in the present study, because they did not use social care services.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are substantial numbers of people with dementia and family caregivers who do not wish to use social care services or apply for certification. 16,17 These participants were classified in the "did not apply" group, and they were assumed to have met the lowest level of care required in the present study, because they did not use social care services. Participants who required nursing care for conditions other than AD or in combination with AD, such as cerebrovascular disease or musculoskeletal disorders, were excluded from this study.…”
Section: Ltci Service Use and Monthly Costsmentioning
confidence: 99%
“…Functional measures included ADLs, IADLs, gait disorders, disability measures, and impairment measures that relate to the World Health Organization’s International Classification of Functioning [24–26]. Other areas of function included measures of cognitive performance, memory, and communication disorders [12, 27–29]. Physical related parameters included sensory loss, hearing loss, communication deficits, pain and other chronic clinical complications [27, 30, 31].…”
Section: Introductionmentioning
confidence: 99%